Sign here - Lux, Claudia (Claudia Kilbourne) (Berkley, 2022)
"A darkly humorous, surprisingly poignant, and utterly gripping debut novel about a guy who works in Hell (literally) and is on the cusp of a big promotion if only he can get one more member of the wealthy Harrison family to sell their soul Peyote Trip has a pretty good gig in the deals department on the fifth floor of Hell. Sure, none of the pens work, the coffee machine has been out of order for a century, and the only drink on offer is Jägermeister, but Pey has a plan-and all he needs is one last member of the Harrison family to sell their soul. When the Harrisons retreat to the family lake house for the summer, with their daughter Mickey's precocious new friend, Ruth, in tow, the opportunity Pey has waited a millennium for might finally be in his grasp. And with the help of his charismatic coworker Calamity, he sets a plan in motion. But things aren't always as they seem, on Earth or in Hell. And as old secrets and new dangers scrape away at the Harrisons' shiny surface, revealing the darkness beneath, everyone must face the consequences of their choices"--